Calibration of various magnitude scales in Turkey using broadband data - Görgün, Ethem. (Thesis (M.S.) - Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2003., 2003)
The local magnitude, ML, for earthquakes of Western Turkey and surrounding regions are determined using synthetic Wood-Anderson seismograms derived from newly available broadband recording from the Boğaziçi University Kandilli Observatory and Earthquake Research Institute (BU KOERI). Seismograms obtained from various types of broadband instruments are transformed to Wood-Anderson type using SAC (Seismic Analysis Code) routines and script files that are developed for this purpose. Wood-Anderson peak amplitudes are measured on 1560 three-component, obtained from 200 earthquakes in the distance range of 8 to 785 km. The earthquakes ranged from ML = 1.0 to 6.4 and were recorded at about 7 stations in the region. ML magnitudes can be obtained from the horizontal and vertical component. Scattering of each ML magnitude in each station is analyzed and their dependence on magnitude and distance are discussed. The station magnitude correction values are found. Some improvements are proposed for the magnitude determination procedures that are actually used at BU KOERI Seismological Laboratory. Finally we have compared our ML computations with the one obtained by other studies using different approaches or different waveform data. We have noted that our results agree well with ML magnitude determinations done at TUBITAK MRC, but deviates significantly from the MD calculations of BU KOERI Seismological Laboratory.
Keywords: Seismology -- Turkey.; Earthquakes -- Turkey.; Broadband amplifiers.